The distance between two points (x₁, y₁) and (x₂, y₂) can be found using the formula:
d = √((x₂ - x₁)² + (y₂ - y₁)²)
In this case, the points are (0, 6) and (-3, -2). Thus, we can substitute these values into the formula:
d = √((-3 - 0)² + (-2 - 6)²)
Simplifying the equation:
d = √((-3)² + (-8)²)
d = √(9 + 64)
d = √73
Rounding to the nearest hundredth, the length between (0,6) and (-3, -2) is approximately 8.54 units.
Apply the Pythagorean Theorem to find the
length between (0,6) and (-3, -2). Round your
answer to the nearest hundredth if necessary.
1 answer